Pengaruh Metode Proyek Terhadap Perkembangan Motorik Halus Anak Kelompok A Di Tk Tunas Sejati Joho Mojolaban Sukoharjo Tahun Ajaran 2015/2016 - Wulandari, Novita Tri; Surtikanti, SH., M.Pd, Dra.Surtikanti, SH., M.Pd (2016)
The purpose of this research is to determine the effect of using project methods on development of fine motor children of group A in TK Tunas Sejati Joho Mojolaban Sukoharjo Academic Year 2015/2016. This research was a kind of experiment with one group pretest-posttest design. The subjects of this research were children of Group A TK Tunas Sejati Joho totaling 15 children. The data collection techniques in this research are using observation, while the technique of data analysis was using descriptive analysis and inferential analysis. Descriptive analysis was used to determine the status of fine motor development of children before and after the experiment while inferential analysis to test the hypothesis was using T test in SPSS 16.0 for windows i.e. Paired sample t-test. Based on the analysis of the research results obtained by using t-test and the value of tcount = -13.436 and ttable = -1.761 with probability 0.000. The probability of 0,000 <α = 0.05, then the null hypothesis was (HO) rejected, which meant there was the influence of the methods of the project on fine motor development of children in group A at TK Tunas Sejati Joho Mojolaban Sukoharjo Academic Year 2015/2016.